Growth, survival and physiological condition of cultured marron, Cherax tenuimanus (Smith, 1912) fed different levels of organic selenium - Nugroho, Rudy; Fotedar, Ravi (David Publishing, 2013)
A 90-day feeding experiment was conducted to evaluate the effects of three levels of dietary supplementation of organic selenium (OS) on physiological and immunological responses of marron (Cherax tenuimanus). Three levels viz. 0.1, 0.2 and 0.3 g kg-1 of basal diet of Sel-Plex® as a source of OS. were prepared and tested against the basal diet, which was used as a control. Each diet was fed to four replicated groups of marron, (initial mean weight of 39.43 ± 0.55 g), at a rate of 3% body weight every second day. At the end of the feeding experiment, dietary inclusion of all Sel-Plex® levels significantly improved specific growth rate (SGR) and survival of marron. Inclusion of Sel-Plex® above 0.1 g kg-1 resulted in significantly higher hepatopancreatic moisture level (HM) and wet hepatosomatic index (Hiw), of marron than marron fed without Sel-Plex. Total Se level in the hepatopancreas was thehighest (5.41 ± 0.28 ?g g-1) in the marron fed 0.2 g kg-1 of Sel-Plex, whereas muscle accumulated significantly higher level of Se when marron were fed 0.3 g kg-1 of dietary Sel-Plex. It is therefore suggested that the beneficial dietary supplementation levels of Sel-Plex in marron should range from 0.2 to 0.3 g kg-1.